Rast kompleksnosti kot smer evolucije? - Makarovič, Matej (Teorija in praksa, 1999)
ABSTRACT: The author emphasises that Spencer and Durheim, and even more clearly Weber and Parsons, have already been sceptical about some assumptions which understand societal evolution as the inevitable progress or the fulfilment of a certain plan. Though human actors and social systems are capable of planning, their planning neither contradicts nor changes the general logic of the evolution based on "blind" variation and selection. Despite some exceptions this logic may, in the long run, generally lead to the survival of the systems with the superior adaptability. Complexity may contribute to greater adaptability, especially if the growth of environmental complexity and Ashby's law of requisite variety are taken into account.
Keywords: družba; society; družbeni sistemi; evolucija; kompleksnost; družbeni razvoj; napredek